Entangled Lines of the Embodied Self: Archie Ferguson’s Urban Experience in Paul Auster’s 4 3 2 1 - Hansen Ira (United Kingdom, 2022)
This article explores how the four interweaving storylines of the contemporary US author Paul Auster’s novel, 4 3 2 1 (2017), create its protagonist Archie Ferguson through his embodied spatial experience of New York City. The starting point is the anthropologist Tim Ingold’s notion that all life is realized as a series of entangling lines, a meshwork of random occurrences, which move to and fro in various directions rather than as a straight line from birth to death. Lines do not merely connect immobile points, such as locations on a map, but rather, are movements along which life is made and revealed. With the help of, for example, de Certeau’s city-texturology, the article shows how the spatial practices of walking and writing (in) the city creates Ferguson’s embodied lifelines. The attentional practices of space – wayfaring – that create Ferguson on the city streets and on the pages of his notebooks weave an environment that permeates Ferguson’s unfolding self, unearthing and giving equal weight to his lived experience and his imagined possibilities. The different layers of Ferguson’s life are not buried under one another in the passing of time, but are amalgamated as his presence to create both Ferguson and the New York that surrounds him on multiple parallel levels.